Asymptomatic torsion of intra-abdominal testis - M. Amin El-Gohary (Elsevier, 2015)
We report a case of intra-abdominal testicular torsion, of eight years old boy who presented with asymptomatic left impalpable testis. Diagnostic laparoscopy revealed a twisted small intra-abdominal testis in which the spermatic cord twisted 3 times over a band attached to the internal ring. The cord was long enough to bring the small testis into the scrotal sac. This case highlights the pole of laparoscopy in the management of impalpable testes.